(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2025)
The rapid development and implementation of digital technologies across various sectors have led to profound changes in the labor market and the sphere of social labor relations. The modern business environment is increasingly shaped by digital solutions, requiring a rethinking of the interactions between employees and employers. Factors such as remote work, flexible schedules, online labor activities, and automation are transforming labor conditions and demanding a reassessment of labor rights and protections. The main objective of this article is to examine the emerging new social labor relations influenced by digital technologies, to identify their opportunities and risks, and to explore ways to enhance the adaptability of human capital in this new environment.